2013
DOI: 10.1108/jiabr-10-2012-0063
|View full text |Cite
|
Sign up to set email alerts
|

Shari'ah disclosures in Malaysian and Indonesian Islamic banks

Abstract: Purpose -The paper aims to contribute to the discussion on Shari'ah governance systems by examining the extent of disclosure on the Shari'ah Supervisory Board (SSB) as well as the content of the Board's report in the annual reports of 23 Islamic banks in Malaysia and Indonesia. The paper also investigates the disclosures about zakat (Islamic levy). Design/methodology/approach -The study is a cross-sectional analysis of annual report disclosures in the year 2009. The paper uses both disclosure indices and conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 38 publications
2
62
2
Order By: Relevance
“…The study has found that no social information is provided in the financial statements of Yemeni Islamic financial institutions. 1 A brief summary of the nature of the bank's activities 2…”
Section: Resultsmentioning
confidence: 99%
“…The study has found that no social information is provided in the financial statements of Yemeni Islamic financial institutions. 1 A brief summary of the nature of the bank's activities 2…”
Section: Resultsmentioning
confidence: 99%
“…At the end of 2016, the Islamic banks in Oman's total market share reached 10.3% of the total banking assets in the Sultanate or equivalent to OMR3.1 billion with 71 branches throughout Oman (Fida et al, 2020). Whereby some countries need 20-30 years in order to have an Islamic banking market share of 5% to 10% such as Malaysia and Indonesia (Abdullah et al, 2013).…”
Section: ~40~mentioning
confidence: 99%
“…Data collection techniques used in this study are documentation and content analysis. Content analysis was developed based on previous research (Abdullah et al, 2013) to measure the disclosure of Islamic governance in Islamic banks in Indonesia. The data analysis method used is path analysis aiming to test the influence of independent variables on IGD.…”
Section: Techniques or Data Collection And Analysismentioning
confidence: 99%